Financial and non-financial impact, and capacity building for an arts festival development – a study of the Kuala Lumpur International Arts Festival (KLIAF) - Yap, Far Loon (2018)
Arts sector development has been much discussed by academics including predicament for many countries’ government to intervene in hope to boost consumption of this merit goods by having long term strategy to include funding, public education and policy reform as part of national agenda. These interventions encompass support in seed funding, arts capacity building, marketing and education pinning the hope that impact both creative economy and spillover effect economic activity to multiple horizontal sectors. This paper focuses Malaysia arts development and is a pilot attempt to identify the capacity building components of arts development eco-system based on the actual annual 5-week event called Kuala Lumpur International Arts Festival (KLIAF) also known as DiverseCity KL 2017. By understanding the capacity building components, the study also examined the impact measure to city of Kuala Lumpur (KL) and greater KL by disclosing both quantitative metrics and qualitative findings in the form of financial and non-financial outcome measures.